ПАРАЛЛЕЛЬ «ПЕТЕРБУРГ – ВЕНЕЦИЯ» В «ЧЕТКАХ» АННЫ АХМАТОВОЙ - Saidat F. Danilova (Philological Studies, 2019)
The article deals with images of St. Petersburg and Venice in the early works of Anna Akhmatova. Purpose of the article is to show that, despite the parallels, the images of St. Petersburg and Venice in the second collection of poems by Anna Akhmatova “Rosary” bear different meanings.